APPLICATION OF CHARACTER EDUCATION WITH CHARACTER - Risal, Muhammad (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2021)
The Indonesian nation intends the formation of a nation's next generation that is morally upright and intellectually intelligent. Numerous examples of pupils who are educated yet lack moral character, and hence cannot be expected to be the nation's future builders. This requires stakeholders to take strategic steps in regulating the education system in Indonesia. As one of the proclaimed character education programs, this program is expected to reintroduce hope for the future of Indonesian education by instilling good values ​​among all involved and as school residents, enabling them to have knowledge, awareness, and action in carrying out character values. As a matter of fact, the concept of good character education will fail if teachers who educate and teach in schools are unable to serve as positive role models for students'